The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1111/j.1553-2712.2010.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Emergency Department Patients with Sickle Cell Pain Crisis: A Learning Collaborative Model to Improve Analgesic Management

Abstract: Objectives: The objectives were to report the baseline (prior to quality improvement interventions) patient and visit characteristics and analgesic management practices for each site participating in an emergency department (ED) sickle cell learning collaborative.Methods: A prospective, multisite longitudinal cohort study in the context of a learning-collaborative model was performed in three midwestern EDs. Each site formed a multidisciplinary team charged with improving analgesic management for patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
0
36
2
Order By: Relevance
“…Several studies in the surgical literature (14,15) have demonstrated the potential for "fast-tracking" postoperative patients with some success. Additionally, in patients with sickle-cell disease, a lot of research in emergency rooms and outpatient and inpatient settings has been focused on developing the best collaborative approach to minimize resource utilization and improve pain control (16)(17)(18). Another significant issue in IBD patients is nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the surgical literature (14,15) have demonstrated the potential for "fast-tracking" postoperative patients with some success. Additionally, in patients with sickle-cell disease, a lot of research in emergency rooms and outpatient and inpatient settings has been focused on developing the best collaborative approach to minimize resource utilization and improve pain control (16)(17)(18). Another significant issue in IBD patients is nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies in the United States of America (USA): Benjamin et al (2000), Tanabe et al (2007) and Tanabe et al (2010) reported achieving initiation within 20 minutes, 90 minutes and 74 minutes, respectively (11,14,15). The results of this survey showed mean times to initiation of analgesic therapy of 38 minutes and 111 minutes at SCU and A&E, respectively.…”
Section: Side Effectsmentioning
confidence: 68%
“…The results of this survey showed mean times to initiation of analgesic therapy of 38 minutes and 111 minutes at SCU and A&E, respectively. Possible reasons for delays in the initiation of therapy proffered by Tanabe et al (14,15) include over-crowding and "under-triage" or the assigning of a lower priority level. Interestingly, negative attitudes toward "frequent attenders" were not cited as a cause for delay by Tanabe et al (14,15).…”
Section: Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The agent does seem to be gaining popularity for use in the ED, for reasons that are both evidence based and anecdotal. The evidence basis for hydromorphone use in the ED is long standing and broad, for indications ranging from renal colic [189] to sickle cell crisis [190]. As for the anecdotal reasons for hydromorphone's growing popularity, some physicians (including this author) have found that hydromorphone use can be a route around inappropriately overcautious nurses who (despite requests to the contrary) split 0.1 mg/kg morphine orders into nearhomeopathic doses administered over 15-30 minutes "for safety. "…”
Section: Hydromorphonementioning
confidence: 99%